Performing agriculture in Post-Soviet Ukraine - Grey, Alastair (2020)
This thesis explores the development of an agricultural market economy in post-Soviet Ukraine, using a theoretical framework based on the social studies of marketisation. Following the dissolution of the Soviet Union, orthodox economists and political commentators have problematised the way in which Ukraine’s transition towards an agricultural market economy has entailed the articulation of market rationale with what are perceived to be contradictory rationalities and logics. Such accounts dismiss Ukraine’s economic development as inauthentic based on a supposed lack of separation between the market and the state, as well as between the formal market and informal or inauthentic forms of production, ownership and exchange. This thesis seeks to challenge these orthodox accounts, exploring the extent to which the social studies of marketisation can be used as an alternative theoretical framework through which to destabilise the notion of Ukraine as a ‘failed transition state’. Based on empirical research that includes in-depth interviews conducted in Kiev with participants working in the spheres of agricultural production, trade and finance, this thesis focuses on the processes of price realisation (Çalişkan, 2007) in two areas of the Ukrainian agricultural economy: (i) the Ukrainian wheat market, and; (ii) Ukraine’s agricultural credit market. Through this research, I demonstrate that Ukraine’s market-orientated transition is better understood not as a passage from one economic order to another, but as a rearrangement in the patterns of multiple orders interwoven with one another. In doing so, I respond to calls for further research that: (i) recognises markets as “diverse arrangements articulated by particular combinations of these rationalities and logics”, and; “regards the determination of their precise articulation and their relative weight as a question that can only be answered empirically” (Berndt’s, 2015:1866). This thesis also provides further empirical examples of the political nature of marking-making in frontier regions (Ouma, 2015) and demonstrates the scope for further application of the marketisation lens to the study of nascent markets in post-Soviet Europe.